Non-Financial Perceptions when Evaluating Financial Performance in the Pandemic Era in Islamic Accounting: Literature Study - Ikhsan Abdullah; Andri Soemitra (International Journal Of Economics Social And Technology, 2022)
In measuring the financial performance of companies with Sharia entities, apart from financial ratios such as profitability, activity, liquidity, and others. Zakat Funds and Islamic Corporate Social Responsibility (ICSR) can be used to measure financial performance. Zakat is an obligation that must be issued. Zakat funds are meant to be zakat funds obtained from the company's net profit, the greater the zakat issued, the greater the company's profit. Islamic Corporate Social Responsibility (ICSR) is a fund that must be issued by the company. There will be a negative response if ISCR funds are not allocated to the community. People trust a company that distributes its ISCR more than a company that does not distribute it. Because large companies will be able to provide ISCR funds to the community. The purpose of this study is to describe the literature on Non-Financial Perceptions when Evaluating Financial Performance in Islamic accounting for a period of five years, 2017-2022. The research method used in this study is qualitative research with content analysis of papers from the Google Scholar database. Researchers found 20 papers, after going through a selection process, the author finally reviewed 13 articles that were considered the most relevant